2013
DOI: 10.4161/chan.25793
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive ion channel TRPV1 is endogenously expressed in the sperm of a fresh water teleost fish (Labeo rohita) and regulates sperm motility

Abstract: (2013) Thermosensitive ion channel TRPV1 is endogenously expressed in the sperm of a fresh water teleost fish (Labeorohita) and regulates sperm motility, Channels, 7:6, 483-492,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
36
1
Order By: Relevance
“…This is especially relevant in salmonids, where sperm movement duration and the associated window for fertilization are extremely short (Kime et al, 2001). In the freshwater teleost Labeo rohita, Ca 2+ influx and consequentially the activation and preservation of sperm movement are regulated by thermosensitive ion channels [vanilloid transient receptor potential (TRPV) channels; Majhi et al, 2013], which may confer heat resistance to the sperm cells, as previously shown for germ cells in mouse testes (Mizrak and van DisselEmiliani, 2008). Changes in heat sensitivity of sperm over the breeding season could be a result of the expression of TRPV channels in sperm cell membranes with advanced maturation of the male trout in our study.…”
Section: Discussionmentioning
confidence: 86%
“…This is especially relevant in salmonids, where sperm movement duration and the associated window for fertilization are extremely short (Kime et al, 2001). In the freshwater teleost Labeo rohita, Ca 2+ influx and consequentially the activation and preservation of sperm movement are regulated by thermosensitive ion channels [vanilloid transient receptor potential (TRPV) channels; Majhi et al, 2013], which may confer heat resistance to the sperm cells, as previously shown for germ cells in mouse testes (Mizrak and van DisselEmiliani, 2008). Changes in heat sensitivity of sperm over the breeding season could be a result of the expression of TRPV channels in sperm cell membranes with advanced maturation of the male trout in our study.…”
Section: Discussionmentioning
confidence: 86%
“…This hypothesis, while not yet demonstrated, is supported by the finding that AQP4 or -5 can interact with the volume sensitive calcium channel transient receptor potential vanalloid 4 (TRPV4) to regulate cell volume under hypotonic stimulation in mouse astrocytes and salivary glands [50,51], and by the direct interaction of AQP2 with actin described in rat kidney cells [52]. In addition, TRP channels have been shown to play functions during sperm capacitation, acrosome reaction motility and fertilization in mammals [53][54][55], as well as to regulate sperm motility in freshwater teleosts [56].…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Two possible candidates are the nonspecific cation channels TRPV1 and TRPV4 (Transient Receptor Potential Vanilloid types 1 and 4, respectively), which have been linked to sperm capacitation, motility, and the AR. [46][47][48][49][50] TRPV1 and TRPV4 have an important physical and functional interaction with TMEM16A, 45,51 in such a way that TMEM16A inhibition produces an important reduction of TRPV1 activation by capsaicin, 45 and TRPV4 activation induces Cl − currents that depend on TMEM16A. 51 In conclusion, this is the first instance of a report of TMEM16A expression in guinea pig sperm.…”
Section: Discussionmentioning
confidence: 63%